MicroRNA-23a and MicroRNA-27a Mimic Exercise by Ameliorating CKD-Induced Muscle Atrophy - Wang, Bin; Zhang, Cong; Zhang, Aiqing; Cai, Hui; Price, S. Russ; Wang, Xiaonan H. (Journal of the American Society of Nephrology, 2017)
Muscle atrophy is a frequent complication of CKD, and exercise can attenuate the process. This study investigated the role of microRNA-23a (miR-23a) and miR-27a in the regulation of muscle mass in mice with CKD. These miRs are located in a gene cluster that is regulated by the transcription factor NFAT. CKD mice expressed less miR-23a in muscle than controls, and resistance exercise (muscle overload) increased the levels of miR-23a and miR-27a in CKD mice. Injection of an adeno-associated virus encoding the miR-23a/27a/24–2 precursor RNA into the tibialis anterior muscles of normal and CKD mice led to increases in mature miR-23a and miR-27a but not miR-24–2 in the muscles of both cohorts. Overexpression of miR-23a/miR-27a in CKD mice attenuated muscle loss, improved grip strength, increased the phosphorylation of Akt and FoxO1, and decreased the activation of phosphatase and tensin homolog (PTEN) and FoxO1 and the expression of TRIM63/MuRF1 and FBXO32/atrogin-1 proteins. Provision of miR-23a/miR-27a also reduced myostatin expression and downstream SMAD-2/3 signaling, decreased activation of caspase-3 and -7, and increased the expression of markers of muscle regeneration. Lastly, in silico miR target analysis and luciferase reporter assays in primary satellite cells identified PTEN and caspase-7 as targets of miR-23a and FoxO1 as a target of miR-27a in muscle. These findings provide new insights about the roles of the miR-23a/27a-24–2 cluster in CKD-induced muscle atrophy in mice and suggest a mechanism by which exercise helps to maintain muscle mass.